Laparoendoscopic Single-Site Hysterectomy in a Morbidly Obese Patient with a Large Uterus: Case Report - Tan, Eunice MX; Goh, Wei-An; Nadarajah (MRCOG), Ravichandran (International Journal of Innovative Research in Medical Science, 2022)
Laparoendoscopic single-site (LESS) hysterectomy has been documented as a well-established method of hysterectomy, allowing for excellent surgical outcomes. Certain patient factors need to be taken into consideration when deciding the approach for hysterectomy. A high body mass index (BMI) can affect the surgical procedure since the thicker abdominal wall may hinder the movement of instruments. With an enlarged uterus, the surgical field may be obstructed which can cause difficulty in obtaining ideal visualisation. The use of LESS can help to overcome these issues, which we demonstrate in our experience of successfully performing LESS hysterectomy in a patient with BMI of 40.6kg/m2 with a severely enlarged uterus of 1609g.